Work-life condition of health work force during COVID-19: A study based on literature review - Hoque, Mohammad Kibria Anamul; Chandhok, Anil; Sunny, Khaled Kalam (International Journal of Business Strategy and Social Sciences, 2023)
The COVID-19 epidemic is proving to be an unparalleled disaster in all facets, including health, sociological, economic, and financial. Aside from the fact that it may have a substantial influence on their health and well-being, health practitioners all over the world have risen to the challenge of treating COVID-19 patients. The primary goal of this research is to examine and evaluate the work-life balance of healthcare personnel during pandemics. This study conducted a systematic evaluation to determine the current situation of health workforces and to assess the impact of COVID-19 on health workforces. This paper began with 70 article reviews. A brief evaluation of 70 publications, 30 articles were chosen for the research based on area and analysis. After examining all of the publications, the study has found that the primary causes of depression, burnout, and suicidal thoughts include workload, anxiety, worry for safety, future earning uncertainty, and panic attack, and sleep disturbance, job stress, exhaustion, and dread. These characteristics affect workers’ physical and mental well-being. Finally, it has an impact on their work-life balance and service quality. Future studies could include additional publications for better results and a review of other sectors. The government and organizations should provide more training, organizational assistance, support for healthcare practitioners’ families, PPE, and mental health services. Regularly monitor the health of the healthcare workers and employ preventative measures. To alleviate work-related stress, higher-level management must recruit extra health personnel.